The prospect of mail-order service as a marketing channel in the Kuala Lumpur and Petaling Jaya area (with respect to Lintasell Sdn Bhd) / Mahmud Dzaki Othman … [et al.] - Othman, Mahmud Dzaki; Husaini, Abu Bakar; Hashim, Ahmad Lutfi; Rashidi, Hamden; Awang Hassim, Norlaila (1984)
Our study is basically to find out the response of consumers to mail-order service as a marketing channel in Kuala"Lumpur and Petaling Jaya area. The research was carried out on the members of Keluarga Ria National, Puri Selera and Wise-Buys. These are mail-order catalogues produced by Lintasell Sdn Bhd. In carrying out our research, we need to know the demographic as well as the habit and attitude of various shopping outlets. Therefore, we had gathered all data necessary and which are relevant to our study. We have categorized Lintasell's products under various sections, such as kitchen-ware, electrical items, stationaries and so forth, 'in each section, we subdivided them under income and marital status. From each of them, we want to know how far the goods promoted are saleable in Kuala Lumpur and Petaling Jaya area. We made a research on non-subscribes as to know their awareness to the existance of mail-order business in Malaysia. We further established this by looking into their respective race and income. Our main focus is on the perception of customers towards Lintasell. In order to have a more precise scenario of the above context, we have made research on subjects of benefits offered, sections in the catalogue, methods of payment and so forth.